JAK2 V617F as a Marker for Long-Term Disease Progression and Mortality in Polycythemia Vera and its Role in Economic Modeling - Jonas Hjelmgren; Kristoffer Nilsson; Gunnar Birgegård (Journal of Health Economics and Outcomes Research)
**Background:** In order to facilitate sound economic evaluations of novel treatments, health-economic models of polycythemia vera (PV) must combine effects on surrogate endpoints in trials with disease progression (DP) and mortality in long-term cohort data.